Microbial Sulfur Biogeochemistry of Oil Sands Composite Tailings with Depth - Kendra, Kathryn E. (My University, 2013)
Surface mining of Alberta’s oil sands has led to significant land disturbance, making reclamation and sustainable development of this resource one of the largest challenges facing the industry today. Syncrude Canada Ltd. has developed an innovative technique to reclaim composite tailings (CT) through constructed wetland landscapes and is currently investigating the viability of a pilot-scale freshwater fen built over sandcapped CT. Unpredicted by abiotic geochemical modelling of CT behaviour, a minor episode of hydrogen sulfide (H2S) gas release was encountered during the initial stages of fen construction indicating microbial activity was likely involved in H2S generation within CT. This thesis investigates the S geochemistry of CT with depth and employed 454 pyrosequencing and functional enrichments to characterize the associated microbial communities in the first S biogeochemical study of oil sands CT. Porewater H2S was detected extensively throughout the deposit with background levels ranging from 14 – 23 µM and a maximum of 301.5 µM detected at 22-24 m of depth. Reduced Fe (Fe2+) was also detected, but confined within surficial depths sampled, ranging from 1.2 – 38.5 µM. Mass balance calculations identify that the Fe2+ generated within the surficial zone of the CT deposit is sufficient to effectively sequester ambient concentrations H2S generated in this deposit through FeS precipitates. Results identifying (1) distinct zones of porewater Fe2+ and H2S, (2) co-occurrence of the highest [H2S] and lowest dissolved organic C (DOC) at 22-24 m consistent with heterotrophic sulfate reducing bacteria (SRB) activity, and (3) the presence of mixed valence Fe biomineral, magnetite, throughout the deposit, are all consistent with microbially-mediated Fe and S cycling occurring within this CT deposit. The cultivation independent identification of several known iron reducing bacteria (IRB) and SRB within CT microbial communities, in conjunction with observed positive growth of IRB and SRB functional metabolic enrichments, demonstrates widespread capacity for microbial Fe and S activity throughout the CT deposit. Metagenomic characterization of CT microbial communities revealed high diversity (over 20 phyla) over the 5 depths examined. Multivariate statistical analyses (Unifrac) revealed that bacterial community composition and structure was driven by changed in DOC, ORP and salinity and that structuring corresponded with a surficial zone of Fe3+ reduction and an underlying zone of SO42- reduction. Despite the high organic carbon (OC) content of oil sands tailings, much of that C is not considered to be labile and accessible to microbes. Based on the results of this thesis, CT SRB appear to have a greater ability than IRB to utilize recalcitrant OC (e.g. bitumen, naphthenic acids) given the widespread occurrence of porewater [H2S] and surficially restricted [Fe2+] despite accessible pools of Fe3+ and OC with depth. This enhanced understanding of biogeochemical S cycling within CT newly establishes the importance of microbial activity in these processes, identifying the need to incorporate microbially based understanding into on-going development of reclamation strategies in order to manage these waste materials effectively.
Keywords: oil sands; composite tailings; sulfur biogeochemistry; metagenomics; Geochemistry; Geochemistry